Comparative Analysis of MySejahtera and SatuSehat Application Use after the COVID-19 Pandemic - Setyaningrum, Intan (Open Access Indonesia Journal of Social Sciences, 2024)
Many aspects have been significantly impacted by the Covid-19 epidemic and the new normal conditions that accompany it. Various innovations in public services follow these changes and become new models for adapting to uncertain times. It is hoped that the availability of digital technology platforms will provide a shortcut and ease in accessing public services as well as efforts to overcome the Covid-19 pandemic. One of them is Malaysia and the Indonesian government which use the MySejahtera and PeduliLindungi application systems. In Indonesia and Malaysia, the COVID-19 epidemic has had a significant impact on the adoption of online digital health applications. This research methodology, also referred to as library research, combines qualitative research techniques with a library study approach. SatuSehat in Indonesia continues to operate nationally covering all regions of the country after the pandemic with new features that have been developed from the previous PeduliLindungi. On the other hand, the use of MySejahtera in Malaysia is currently only intended for people who have been verified as positive for Covid-19, which is used to update the quarantine period.